Big Data: Are Accounting Educators Ready? - Pandula Gamage (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This paper explores the latest developments in Big Data and its impact on accounting education. As such, it reviews Big Data developments with specific reference to the accounting profession. It also presents some of the initiatives taken by the professional accounting bodies and universities to address Big Data topics in the accounting curriculum. The findings suggest that Big Data will have an impact on the future role of accounting professionals. Therefore, this study proposes that Big Data topics be embedded in existing courses across accounting curricula to prepare twenty-first-century accounting professionals with skills related to Big Data analytics.
Keywords: M41; 650; Big Data; accounting curriculum; accounting education